Renewal and Retraditionalisation - Adam Diderichsen (Nordisk Politiforskning)
Abstract This paper analyses the prehistory and short existence of the Danish bachelor’s degree programme in policing. I argue that both the development and the implementation of the programme were characterised by a systematic decoupling of the educational reform from the strategic objectives that it was supposed to accomplish. This explains the programme’s early demise in the politically tense situation that arose in the fall of 2015. However, since the study programme was originally intended as the concluding element in the 2007 police reform, I also argue that the recent restructuring of police training is part of a more general reorientation of Danish policing away from the objectives of the 2007 reform.,